2017
DOI: 10.1007/s13524-017-0629-4
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Disparities: The Impact of the Great Depression and Cumulative Inequality on Later-Life Cognitive Function

Abstract: Population aging has driven a spate of recent research on later-life cognitive function. Greater longevity increases the lifetime risk of memory diseases that compromise the cognitive abilities vital to well-being. Alzheimer's disease, thought to be the most common underlying pathology for elders' cognitive dysfunction (Willis and Hakim 2013), is already the sixth leading cause of death in the United States (Alzheimer's Association 2016). Understanding social determinants of pathological cognitive decline is k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 119 publications
1
14
0
Order By: Relevance
“…We offer only a brief overview of these risk factors, as they have been reviewed extensively elsewhere (e.g., Livingston et al, 2017 ). Evidence suggests that early-life SES and/or exposure to hardship are associated with both early-life cognitive development ( Currie, 2009 ; Torche, 2018 ) and later-life cognitive decline, even net of intervening life-course risk factors ( Hale, 2017 ). Consistently, the most important modifiable predictor of cognitive function is educational attainment ( Leggett et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…We offer only a brief overview of these risk factors, as they have been reviewed extensively elsewhere (e.g., Livingston et al, 2017 ). Evidence suggests that early-life SES and/or exposure to hardship are associated with both early-life cognitive development ( Currie, 2009 ; Torche, 2018 ) and later-life cognitive decline, even net of intervening life-course risk factors ( Hale, 2017 ). Consistently, the most important modifiable predictor of cognitive function is educational attainment ( Leggett et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Using the Health and Retirement Study, Luo and Waite (2005) showed that older adults who grew up with parents with less than 8 years of school have lower levels of cognitive function than those who did not. Nutritional deprivation and poverty, likewise, appear to have negative long-term effects (Barnes et al, 2012; Hale, 2017). Research also shows that early experiences shape the progression of cognitive decline; cognitive function across multiple domains drops most precipitously over a 12-year period for those growing up in disadvantaged homes (Lyu & Burr, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Cognitive function plays a crucial role in the daily life function of older adults, and it is a clear indicator of mental health and well-being in this population. 6 Poor cognitive function among older adults is a precursor to dementia, the global cost of which is approximately US$818 billion. 7 Currently, dementia is not curable.…”
Section: Introductionmentioning
confidence: 99%